Philippine eSports Convention Center - Librada, Richard Jr. C.
eSports as a source of tourism has never been done in the Philippines. As proof of this, there is no existing structure that has been designed specifically to cater to the needs of major eSports events. This project aims to design structure equipped to handle major eSports events by providing the spaces needed for tournaments and events. The design is basically 3 halls and an atrium in the middle as told be able to provide for multiple genres of games as well as have enough adaptability to host other events. It should also cater to both private and public transportation to help give access to the relatively high aim of 800 people as the audience per hall. As a project, it will be one of the few who use the relatively new industry that is eSports as a main target audience and may give insight to possible standards for future structures build for the same purpose. Plausibility of the project, audience size to consider, lobby sizes and possible layout would be the major findings that this project will show as well as some insight into unusual building shapes.